Pengaruh NAA, 2-4-D dan Pencahayaan Terhadap Pembentukan Kalus pada Kultur Jaringan Daun Nilam (Pogostemon cablin Benth.) - Easy Harnelly; Zairin Tomy; Syarifah Fadiya Hallaby (Jurnal Agrista, 2006)
The Influence of NAA, 2-4-D and Lightness on Callus Development of Nilam Leaf (Pogostemon cablin Benth.) Tissue CultureABSTRACT. The research about the influence of NAA, 2-4-D and lightness on callus development of nilam’s leaf (Pogostemon cablin Benth.) Tissue culture had been done in cell and Molecular Biology Laboratory, Science Faculty of Syiah Kuala University, Darussalam, Banda Aceh since April to October 2006. This research using factorial experimental design with three factor (kind of auxin, auxin concentration and lightness). The result showed that kinds of auxin had not had any significant influence to callus development, but lightness and auxin concentration influence the callus development. Darkness treatment and the rise of auxin concentration increased to callus development.